THE IMPACT OF VELOCITY OF MOVEMENT ON PERFORMANCE FACTORS IN RESISTANCE EXERCISE - HATFIELD, DISA L.; KRAEMER, WILLIAM J.; SPIERING, BARRY A.; HÄKKINEN, KEIJO; VOLEK, JEFF S.; SHIMANO, TOMOKO; SPREUWENBERG, LUUK P.B.; SILVESTRE, RICARDO; VINGREN, JAKOB L.; FRAGALA, MAREN S.; GÓMEZ, ANA L.; FLECK, STEVEN J.; et al. (Journal of strength and conditioning research, 2006)
The purpose of this study was to determine the impact of a very slow (VS) velocity and a self-selected volitional (VOL) velocity at varying intensities on repetition number, peak force, peak power, and total volume in the squat and shoulder press exercises. On separate testing days, 9 resistance trained men (age23.9 ± 2.5 years; height174.8 ± 6.5 cm; body mass80.1 ± 12.4 kg) performed a squat (SQ) and shoulder press (SP) exercise at 60 or 80% of 1 repetition maximum (1RM) at either VOL or VS (10-second eccentric and 10-second concentric actions) velocity for as many repetitions as possible. Force, power, and volume (repetitions × kg) were also determined. Subjects performed significantly fewer repetitions (p ≤ 0.05) in the VS exercises (60% VS SQ 5 ± 1 vs. VOL SQ 24 ± 2; 80% VS SQ 2 ± 0 vs. VOL SQ 12 ± 1; 60% VS SP 4 ± 1 vs. VOL SP 14 ± 2; 80% VS SP 1 ± 0 vs. VOL SP 6 ± 1). Peak force and power were significantly higher at the VOL speed (peak force [in newtons]60% VS SQ 564.4 ± 77.3 vs. VOL SQ 1229.0 ± 134.9 N; 80% VS SQ 457.3 ± 27.9 vs. VOL SQ 1059.3 ± 104.7 N; 60% VS SP 321.6 ± 37.8 vs. VOL SP 940.7 ± 144.8 N; 80% VS SP 296.5 ± 24.7 vs. VOL SP 702.5 ± 57.7 N; and peak power [in watts]60% VS SQ 271.2 ± 40.1 vs. VOL SQ 783.2 ± 129.1 W; 80% VS SQ 229.3 ± 49.5 vs. VOL SQ 520.2 ± 85.8 W; 60% VS SP 91.3 ± 21.9 vs. VOL SP 706.6 ± 151.4 W; 80% VS SP 78.1 ± 19.8 vs. VOL SP 277.6 ± 46.4 W). VOL speed elicited higher total volume than the VS velocity. The results of this study indicate that a VS velocity may not elicit appropriate levels of force, power, or volume to optimize strength and athletic performance.